2008
DOI: 10.1007/s11248-008-9232-1
|View full text |Cite
|
Sign up to set email alerts
|

Mice transgenic with SV40-late-promoter-driven Polyomavirus Middle T oncogene exclusively develop hemangiomas

Abstract: In order to develop a model system of infantile hemangioma, transgenic mice were developed carrying the Polyomavirus Middle T (PyMT) gene driven by the SV40 late promoter. From the 520 fertilized eggs surviving microinjection, there were 25 live births. Three of these showed the hemangioma phenotype and carried and expressed the PyMT gene; the remaining descendants were normal. The tumors showed abnormal vascular proliferation with cavernous hemangioma-like structures in the skin surface, tongue, ear mucosa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Many studies have shown that PyMT is a key player in the growth of tumors and can cause cell death in vitro, which can lead to benign and malignant tumors in organs such as the skin, salivary gland, and mammary gland of mice [ 69 , 70 ]. Xu et al [ 71 ] made an IH animal model by microinjecting the PyMT transgenic DNA of polyomavirus into fertilized embryos, transferring them to mice that looked like they were pregnant, and observing the tumors in the newborn mice’s phenotypes and histological shapes (Fig. 3 ).…”
Section: Transviral and Genetic Modelsmentioning
confidence: 99%
“…Many studies have shown that PyMT is a key player in the growth of tumors and can cause cell death in vitro, which can lead to benign and malignant tumors in organs such as the skin, salivary gland, and mammary gland of mice [ 69 , 70 ]. Xu et al [ 71 ] made an IH animal model by microinjecting the PyMT transgenic DNA of polyomavirus into fertilized embryos, transferring them to mice that looked like they were pregnant, and observing the tumors in the newborn mice’s phenotypes and histological shapes (Fig. 3 ).…”
Section: Transviral and Genetic Modelsmentioning
confidence: 99%
“…Many studies have claimed to have a mouse model of hemangioma. A transgenic mouse with SV40 promoter-driven Polyomavirus Middle T gene demonstrated abnormal vascular proliferation with cavernous hemangioma-like structures in the skin, tongue, ear and gastric mucosa (Xu et al, 2009). The authors of this paper claimed that this was a model for IH; however, these tumors did not involute.…”
Section: Past Studiesmentioning
confidence: 99%
“…To investigate the etiology of this disease, we and others reported a transgenic model of hemangioma that expresses the polyoma middle T antigen (PyMT), the principal oncoprotein of the murine polyomavirus. The transgenic mice were characterized by spontaneous hemangiomas [ 3 , 4 ]. However, there are still some unresolved problems in this model that limit its application.…”
Section: Introductionmentioning
confidence: 99%